2022
DOI: 10.1097/gox.0000000000004549
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological and Neuroplastic Changes in Postamputation and Neuropathic Pain: Review of the Literature

Abstract: Background: Despite advancements in surgical and rehabilitation strategies, extremity amputations are frequently associated with disability, phantom limb sensations, and chronic pain. Investigation into potential treatment modalities has focused on the pathophysiological changes in both the peripheral and central nervous systems to better understand the underlying mechanism in the development of chronic pain in persons with amputations. Methods: Presented in this article is a discussion outlining the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Pain following limb amputations is thought to be mediated by the NMDA receptor, which is one of the primary excitatory neurotransmitters that carry pain signals from the dorsal horn to the brain. 21,22 The activation of this receptor causes neuronal sensitisation, leading to hyperalgesia, neuropathic pain and reduced opioid R.S. Qureshi, T. Alam, A.W.…”
Section: Discussionmentioning
confidence: 99%
“…Pain following limb amputations is thought to be mediated by the NMDA receptor, which is one of the primary excitatory neurotransmitters that carry pain signals from the dorsal horn to the brain. 21,22 The activation of this receptor causes neuronal sensitisation, leading to hyperalgesia, neuropathic pain and reduced opioid R.S. Qureshi, T. Alam, A.W.…”
Section: Discussionmentioning
confidence: 99%
“…Doing so blocks calcium influx, limiting the neuron's ability to release glutamate and P into the synapse. Furthermore, studies have suggested that pregabalin may help reduce spontaneous nerve firing in damaged nerve fibers within the stump and adjacent fibers in patients with PLSynd (35).…”
Section: Discussionmentioning
confidence: 99%
“…Increased excitability of sensory neurons is due to reduction of activation threshold of their ion channels, which may be caused by nerve injury, inflammation (arising from both neural and non-neural tissue), and by ion channel mutations ( 68 , 78 , 79 ). Although there are many mechanisms involved in sensitization, abnormal peripheral neuronal activity plays a key role as a triggering input ( 25 , 26 , 80 ). In this regard, nociceptive sensitization can electrophysiologically be understood as ongoing (spontaneous) activity and mechanical sensitivity of primary sensory fibers ( 81 ), which relates to neuronal hyperexcitability.…”
Section: Pre-hypothetical Reasoning: Ectopic Nociceptive Sensitizatio...mentioning
confidence: 99%